KEWENANGAN PENGAWAS PEMILIHAN UMUM DALAM PELANGGARAN ADMINISTRATIF - Robert Hoffman (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2018)
After the Law of the Republic of Indonesia Number 7 of 2017 concerning General Elections was ratified by the President of the Republic of Indonesia, Joko Widodo, on August 15, 2017 and promulgated by the Minister of Law and Human Rights of the Republic of Indonesia, Yasonna Laoly, on August 16, 2017, there were changes to the regulation regarding the holding of general elections (Elections). One of these changes is the granting of authority to the Election Supervisory Body (Bawaslu), Provincial Bawaslu, and Regency / City Bawaslu in election administrative violations in the form of receiving, examining, reviewing and deciding election administrative violations. This is as stated in Article 461 paragraph (1) of the Republic of Indonesia Law Number 7 of 2017 concerning General Elections. The approach method used in this study is normative juridical. The results of this study indicate that the Election Supervisory Body (Bawaslu), Provincial Bawaslu, and Regency / City Bawaslu in election administrative violations have attribution authority in the form of receiving, examining, reviewing and deciding election administrative violations. Conclusions from the results of this study that the authority of election supervisors in administrative violations is based on the laws and regulations, namely the 1945 Constitution of the Republic of Indonesia; Republic of Indonesia Law Number 7 of 2017 concerning General Elections; and Regulation of the General Election Supervisory Agency Number 8 of 2018 concerning Settlement of Election Administration Violations and based on legal principles covering the principles of direct, public, free, confidential, honest and fair; the principle is done openly; and fast, impartial, and open principles and obstacles to the authority of the electoral supervisor in administrative violations are found in the components of substance, structure and legal culture, so that they have not been implemented effectively.